(untitled) (Western European Journal of Historical Events and Social Science, 2023)
This article examines the modern problems of educating students that arise in the field of higher education. The emergence of socially vulnerable groups of youth and the simultaneous cultivation of the elitism of others led to the growth of individualism in its acute manifestations.